Fungsi Media Online Sebagai Media Literasi Budaya Bagi Generasi Muda - Aprinta, Gita (Universitas Semarang, 2013)
Online media as an alternative media expected to fulfill the function of the mass media as the previous conventional media, among others, to meet the needs of information all at once into a medium that is able to educate its users. A website called www.palingindonesia.com seeks to encourage young people to participate actively to share the experience and knowledge of Indonesian culture through writing. Using a qualitative content analysis this study aims to identify the educational messages on website www.palingindonesia.com with the conception of internet and public sphere as a ground theory that focusing texts as an object. Mayring methods is choosen to analyze the text by combined lexico grammatical, context analysis, and intepretation. This study resulted a conclusion that the function of culture media literacy can be run on online media www.palingindonesia.com